Template-assisted electrodeposited cupric oxide nanotubes and hierarchical nanospikes for tailoring electrode-electrolyte interfacial charge transfer. Issue 24 (15th December 2021) - Yar, Asfand; Krishnan, Syam G.; Dennis, John Ojur; Khalid, Mohammad; Jose, Rajan
Abstract: Morphological modification in materials aids multi-channel electron access sites for easier electrolyte ion access for many electrochemical devices including energy storage devices. Controlled synthesis of such multichannel morphologies of metal oxides offers significant challenges. Herein, we report a template-assisted electrodeposition technique for the synthesis of Cu nanowires, which are transformed into either CuO nanotubes by controlled annealing or CuO hierarchical nanospikes using a simple hydroxyl ion impregnation technique and subsequent annealing. These materials are tested as electrodes in charge storage systems in 6 M KOH electrolyte in a three-electrode system; both electrodes have shown battery-type charge storage behaviour. Despite the chemical similarity between the two materials, the CuO nanospikes electrodes showed improved charge transport between electrode-electrolyte interface compared to the CuO nanotubes. With the cost-effectiveness, easy availability, and multi-channel morphology of CuO nanospikes along with the promising performance of the electrode in a three-electrode system, the present research offers future potential in developing low cost and high performing energy storage devices.